Immunological aspects of corneal transplant. (November 2014) - Kumar, Vijay; Kumar, Asha
<x xml:space="preserve">Abstract</x> Corneal transplant is the most common solid tissue transplant in humans. Advances in microsurgical techniques, eye banking and the use of corticosteroids have improved the success of corneal transplants. Over 65, 000 corneal transplants are being performed worldwide annually. Most of these transplants are performed in developed countries. Cornea is considered an immune privileged site. Despite this, immune mediated graft rejection is the most single cause of cornea graft failure and is one of the major postoperative complications. Incidences from as low as 2% to as high as 50% have been reported depending upon the degree of vascularization. Rejection involves donor tissue recognition and various factors may influence this rejection. Major factors include the antigenic load of the donor tissue; other factors include death to enucleation time, methods and temperature of preserving the tissue. Host factors that may impact the graft include ocular surface diseases such as dry eye, chemical burns and autoimmune diseases such as mucous membrane pemphigoid. Following infection, surgery or trauma, cells of the innate immune system invade the cornea as a result of up-regulation of cytokines, cellular adhesion molecules and growth and angiogenic factors. These factors results in neoangiogenesis and lymphoangiogenesis, leading to immune activation and graft rejection. The various immunological mechanisms that may play a role in the corneal transplant are discussed.